Pengaruh Penambahan Starbo-AFE Terhadap Kualitas Kompos Berbahan Dasar Feses Sapi, Gamal, Pelepah Sawit, Serbuk Gergaji, Dan Dedak - Muhammad Jurnalis; Adriani; Yurleni (PT. Hasba Edukasi Mandiri, 2025)
This study aimed to determine the effect of Starbo-AFE addition on the nutrient quality of compost made from cow feces, gamal leaves, oil palm fronds, sawdust, and rice bran. The design used in this study was a Completely Randomized Design (CRD) with 4 treatments and 4 replications. The treatments consisted of: P0 = 50% cow feces + 20% gamal + 23% oil palm fronds + 5% sawdust + 2% bran, P1 = 50% cow feces + 20% gamal + 23% oil palm fronds + 5% sawdust + 2% bran + 2% Starbo-AFE, P2 = 50% cow feces + 20% gamal + 23% oil palm fronds + 5% sawdust + 2% bran + 4% Starbo-AFE, P3 = 50% cow feces + 20% gamal + 23% oil palm fronds + 5% sawdust + 2% bran + 6% Starbo-AFE. The parameters observed in this study were the physical form of the compost (odor, color, and texture), temperature, and the nutrients of the compost produced (C, N, and C/N ratio). The results of the study showed that the physical form of the compost was in the good category, producing a blackish brown color, an earthy compost odor, and crumbly textured compost in each treatment (P0, P1, P2, and P3). The average temperature of the composting process in all treatments was 32.30C. The results of the statistical analysis showed that the addition of Starbo-AFE had no significant effect (P>0.05) on the carbon content (29.1%), nitrogen (3.44%), and C/N ratio of the compost (8.55%). Based on the research results, it can be concluded that the addition of Starbo AFE in making compost from cow feces, gamal, oil palm fronds, sawdust, and bran from all treatments produces compost with relatively uniform compost quality and meets the compost quality standards set by SNI 19-7030-2004.